Genetic diversity and relationships among Lyle's flying fox colonies in Thailand - Sukgosa, Ngamphrom; Duangjai, Sutee; Duengkae, Prateep; Wacharapluesadee, Supaporn; Songmongkol, Pimchanok; Yingsakmongkon, Sangchai; Olival, Kevin J.; Hemachudha, Thiravat (Agriculture and Natural Resources, 2018)
Lyle's flying fox (Pteropus lylei) is a large frugivorous bat found in central Thailand that usually roosts in temples in the middle of towns in close proximity to humans. Pteropus lylei is considered a reservoir for Nipah encephalitis viral outbreaks reported in Malaysia and Bangladesh. Thailand is bordered to the south by Malaysia. Information on the genetic diversity and genetic relationships of P. lylei is limited; therefore, cytochrome b (cytb) DNA sequences were used to examine the genetic diversity and genetic relationships of P. lylei. In total, 52 P. lylei individuals from 10 colonies in central Thailand were analyzed. The study identified 25 unique haplotypes and 43 variable sites among the 52 individuals. The results showed that P. lylei had high levels of haplotype diversity (0.949, 25 different haplotypes among 52 individuals) but low levels of nucleotide diversity (0.006). The overall pairwise 4ST was 0.006 (p < 0.05). The results indicated that high levels of gene flow occurred among P. lylei colonies distributed across central Thailand. The sequence data suggested that the overall P. lylei population has high levels of haplotype diversity, which may reflect genetic exchange during P. lylei movement. These results will help manage populations and assess the risk of outbreaks of the encephalitis (Nipah) virus carried by Lyle's flying fox.